Enlargement Of Wallago Leeri With Fish Meal Combination - Evi Rianti; Usman M. Tang; Iskandar Putra (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from February to April 2014, for 60 days inexperiment pondof Fisheries Faculty and Marine Sciences, University ofRiauPekanbaru.The aims of the research was todetermine the effect of fish mealcombinations on the growth and survival of Wallago leerireared in ponds.TheMethod used was experiment with3 treatments and 3 replications. The treatmentswereP1= 25% fish trash + 75% pellet, P2 = 50% fish trash + 50% pellet, P3 = 75%fishtrash + 25% pellet.The best result was treatmentP3 with absolute growthweights (11,23 g), absolute growth length (4,50 cm), daily growth rate (0,34%)and survival rate 90 %.Key words : Wallago leeri,fish meal combination, fish trash and pellet.